A Polyamine Oxidase from Selaginella lepidophylla (SelPAO5) can Replace AtPAO5 in Arabidopsis through Converting Thermospermine to Norspermidine instead to Spermidine - Sagor, G. H. M. (Plants (Basel), 2019)
Of the five polyamine oxidases in Arabidopsis thaliana, AtPAO5 has a substrate preference for the tetraamine thermospermine (T-Spm) which is converted to triamine spermidine (Spd) in a back-conversion reaction in vitro. A homologue of AtPAO5 from the lycophyte Selaginella lepidophylla (SelPAO5) back-converts T-Spm to the uncommon polyamine norspermidine (NorSpd) instead of Spd. An Atpao5 loss-of-function mutant shows a strong reduced growth phenotype when growing on a T-Spm containing medium. When SelPAO5 was expressed in the Atpao5 mutant, T-Spm level decreased to almost normal values of wild type plants, and NorSpd was produced. Furthermore the reduced growth phenotype was cured by the expression of SelPAO5. Thus, a NorSpd synthesis pathway by PAO reaction and T-Spm as substrate was demonstrated in planta and the assumption that a balanced T-Spm homeostasis is needed for normal growth was strengthened.